Purification System of Ocean Sludge by Using Coagulants and Activating Microorganisms - Kyoichi OKAMOTO; Kenji HOTTA (GEOMATE Journal, 2013)
Ocean sludge exerts a very big environmental load to local sea area. Here, attention was paid to micro-bubble technology for application to the purification of the sludge. The important point in this technique is to activate the bacteria existing in the area by micro-bubbles. We had developed a method for decomposing the sludge by using of microorganisms in an aerobic state by micro-bubble. Here, we have also a technique for purification by using “coagulants”. So, we proposed the experimental way which hydrogen sulfide is reduced at first by using “coagulants” and then the nutrients will be reduced by activating microorganisms. Here, we used the detergents including enzyme as the microorganism activator. Our research object in this paper is to check the purification performance for sludge by our proposed experimental system. From the results of our experiments, we succeeded in reducing the time needed to purify the sludge, and we obtained the very good performance